Restraint of Trade Clause in the Digital Economy: South African and Islamic Law Comparison - Carlos Joel Tchawouo Mbiada (Asy-Syari'ah, 2025)
Abstract: A Restraint of Trade clause stands between employers to safeguard legitimate protectable interests and the employee's right to exercise a profession freely. Therefore, this research aims to conduct a comprehensive examination into enforcing restraint of trade agreements in South Africa, critically analyzing the judiciary's balance between the legitimate protectable interests of employers and the constitutionally enshrined right of employees to freedom in occupation and profession. A doctrinal review of key South African case law is carried out, where judicial enforcement depends on a value judgment between public policy and contractual freedom, particularly under section 22 of the Constitution. Furthermore, this research engages with the Islamic legal framework on restraint of trade, drawing on foundational concepts such as hurriyat al-kasb (freedom to engage in lawful trade), gharar (prohibition of uncertainty), and the ethical obligations embedded in shurut (contractual conditions). The results show that Islamic jurisprudence imposes strict moral limitations to ensure no clause unjustly inhibits a worker’s right to earn a lawful livelihood while acknowledging the sanctity of contracts. Selected Islamic countries legally approach restraint of trade clauses within a legal system grounded in Sharia principles and statutory law as reported through a comparative analysis. The implications of restraint clauses are also assessed in the context of a digitalized economy, where traditional notions of geographic and jurisdictional limits become blurred. In the absence of precedent, South African courts can rely on territoriality (place of work) or nationality principles (parties’ origin) to determine jurisdiction over cross-jurisdictional digital labor disputes. The contribution advocates for the creation of a robust legal framework to address restraint enforcement in virtual environments, striking a balance between innovation-driven business protection and the fundamental rights of workers under constitutional and Islamic legal traditions.